Development of Microcontroller-Based Free Fall Motion Learning Materials to Increase Students’ Conceptual Understanding - Infianto Boimau; Ruth Novi Kornalia Mellu (STKIP Singkawang, 2019)
Students’ shortcoming in understanding various concepts of physics is often due to the lack of teaching media can promote student active participation in the learning process. This study aims to develop a valid and effective microcontroller-based physics learning materials as teaching media in enhancing conceptual understanding of free fall motion lessons. This learning materials is developed using the research and development (R&D) method. Effectiveness test of learning materials using pre-experimental research design one group pretest-posttest involve students of physics education program in STKIP SoE. Data collection techniques were done through validation sheets, observations, test questions, and questionnaire sheets. Validation of learning materials through expert testing shows that learning materials are in a valid category. The results of the study shows that learning materials have a positive effect in improving students' conceptual understanding. The effectiveness of the use of learning materials in improving students' understanding of concepts has been analyzed through the results of N-gain calculations which show a moderate score increase. Moreover, the practicality test of learning materials using a Likert scale shows that learning materials are very practical to utilize as teaching media.